The short story of Sang Pemimpin as a means of conflict resolution - Amalia, Triana; Sapriya, Sapriya; Effendi, Ridwan (JIPSINDO, 2024)
Conflict is unavoidable, especially for Generation Z who are currently studying at the junior high school level. They are always familiar with the internet and social media and tend to avoid conflicts with family, friends or in the surrounding environment. Researchers focus on Conflict resolution skills included in the dimensions of social participation skills in social studies learning. This research aims to determine how effective the short story media "Sang Pemimpin" by Sori Siregar is on the conflict resolution skills of students at SMP Negeri 1 Cibadak. The research method used was a quasi-experiment with a nonequivalent control group design. The analysis techniques used are the Kolmogorov-Smirnov normality test and hypothesis testing using the t-test. The research results showed that the use of social studies learning media in the form of a short story entitled "Sang Pemimpin" in class experimental class was more effective as seen in the post-test results with an average of (165.38). Meanwhile, the post-test results from the control class only used media in the form of news articles in the social studies textbook, getting post-test results with an average of (146.81). It is hoped that the findings of this research will increase the variety of social studies learning media such as printed reading media